NPK Fertilizer Test and Plant Population on The Growth And Years of Sorgum (Sorghum bicolor (L.) Moench) - Triyono, Kharis; Priyono, Priyono; Agustina, Wahyu (Journal of World Science, 2023)
This study aims to determine the effect of NPK fertilizer dose and plant population on the growth and yield of Sorghum (Sorghum bicolor (L.) Moench).The design that was carried out was a Complete Randomized Block Design (RAKL) Factorial consisting of  NPK fertilizer dose treatment with four levels and the second-factor Spacing with two levels, so there are eight treatment combinations repeated four times. The data obtained were analyzed by analysis of variance and to find out significant differences continued with Duncan's Multiple Range Test with a significant level of 5%. The results showed that the fertilizer dose treatment had a significant effect on plant height and seed weight per panicle, the plant population treatment had no significant effect on all observed parameters, and the combination of fertilizer dose and population treatments had no significant effect on all observed parameters. The treatment with a fertilizer dose of 300 kg/ha produced the highest seed weight per panicle of 91.79 gr, and the lowest fertilizer dose of 150 kg/ha produced a seed weight per panicle of 71.95 gr.